Prevalence of Depression in Survivors of Acute Myocardial Infarction: Review of the Evidence - Thombs, Brett D (Blackwell Science Inc, 2006)
OBJECTIVES: To assess the prevalence and persistence of depression in patients with acute myocardial infarction (AMI) and the relationship between assessment modality and prevalence. DATA SOURCES: MEDLINE(®), Cochrane, CINAHL(®), PsycINFO(®), and EMBASE(®). REVIEW METHODS: A comprehensive search was conducted in March 2004 to identify original research studies published since 1980 that used a standardized interview or validated questionnaire to assess depression. The search was augmented by hand searching of selected journals from October 2003 through April 2004 and references of identified articles and reviews. Studies were excluded if only an abstract was provided, if not in English, or if depression was not measured by a validated method. RESULTS: Major depression was identified in 19.8% (95% confidence interval [CI] 19.1% to 20.6%) of patients using structured interviews (N=10,785, 8 studies). The prevalence of significant depressive symptoms based on a Beck Depression Inventory score ≥10 was 31.1% (CI 29.2% to 33.0%; N=2,273, 6 studies), using a Hospital Anxiety and Depression Scale (HADS) score ≥8%, 15.5% (CI 13.2% to 18.0%; N=863, 4 studies), and with a HADS score ≥11%, 7.3% (CI 5.5% to 9.3%; N=830, 4 studies). Although a significant proportion of patients continued to be depressed in the year after discharge, the limited number of studies and variable follow-up times precluded specification of prevalence rates at given time points. CONCLUSIONS: Depression is common and persistent in AMI survivors. Prevalence varies depending on assessment method, likely reflecting treatment of somatic symptoms.